Variation in the UCP2 and UCP3 genes associates with abdominal obesity and serum lipids: The Finnish Diabetes Prevention Study - Ilanne-Parikka Pirjo; Aunola Sirkka; Valle Timo T; Eriksson Johan G; Tolppanen Anna-Maija; Kolehmainen Marjukka; Lindström Jaana; Pulkkinen Leena; Salopuro Titta; Keinänen-Kiukaanniemi Sirkka; Tuomilehto Jaakko; Laakso Markku; et al. (BMC, 2009)
Abstract Background We explored the associations of three variants in the uncoupling protein 2 (UCP2) gene, one variant in the UCP2-UCP3 intergenic region and five variants in the uncoupling protein 3 (UCP3) gene with obesity and diabetes related traits in subjects with impaired glucose tolerance participating in Finnish Diabetes Prevention Study. Altogether 507 overweight individuals (body mass index: 31.2 ± 4.5 kg/m2, age: 55 ± 7 years) for whom DNA was available were randomized to either an intensified diet and physical activity group or to a conventional care control group. Methods We analysed the data from the baseline and annual follow-up visits from years 1, 2 and 3. Measurements of anthropometry, plasma glucose and serum insulin in oral glucose tolerance test, serum total cholesterol, HDL-cholesterol and triglycerides were included. The median follow-up time for type 2 diabetes incidence was 7 years. Genetic variants were screened by restriction fragment length polymorphism or Illumina method. Results UCP3 gene variant rs3781907 was associated with increased serum total and LDL-cholesterol levels, at baseline and during the follow-up period. The same variant was associated with a higher risk of type 2 diabetes. Variants rs1726745, rs11235972 and rs1800849 in the UCP3 gene associated with serum total and LDL-cholesterol at baseline. Haploblock including variants rs659366, rs653529, rs15763, and rs1726745 was associated with measures of abdominal obesity at baseline and in the longitudinal analysis. The haplotype comprising alleles rs659366-G, rs653529-A, rs15763-G and rs1726745-A was associated with higher waist-to-hip ratio, and haplotype comprising alleles rs3781907-G, rs11235972-A, and rs1800849-T was associated with increased serum total and LDL-cholesterol concentrations. Conclusion Genetic variation in the UCP2-UCP3 gene cluster may act as a modifier increasing serum lipid levels and indices of abdominal obesity, and may thereby also contribute to the metabolic aberrations observed in obesity and type 2 diabetes.